Harmonics Analysis at Low Voltage (LV) Systems in Universiti Teknologi PETRONAS (UTP) - Mohd Ala’uyun, Husna Khalilah (Universiti Teknologi PETRONAS, 2017)
Harmonics has been part of power quality problem since years ago. Harmonics is stated as the frequency which is a multiple integer of its fundamental frequency of 50 Hz or 60 Hz. There are three groups of harmonic which include positive, negative and zero sequence harmonic. Today, the usage of non-linear loads which contribute in producing a distorted waveform is increasing and it is a serious matter to maintain the quality of voltage and current waveform. This research focused on analysing and identifying the harmonics content at low voltage (LV) system in Universiti Teknologi PETRONAS (UTP). In this research, the levels of harmonics are measured at the point of common coupling (PCC) where the data taken are using the power quality analyser. These data are analysed to identify the sources of harmonics.